ANALISIS INTEGRASI PASAR IKAN CAKALANG DI KABUPATEN HALMAHERA SELATAN, PROVINSI MALUKU UTARA - Fauji Yamin; Anna Fariyanti; Siti Jahroh (Journal of Food System & Agribusiness, 2020)
This study was aimed to analyze the integration of vertical cakalang fish markets at the fishermen level, wholesalers, and retailers in Ternate city and Bitung city. Monthly time series data for the 2015-2019 period were used for this research. The analytical method used was Johansen's cointegration, Granger Causality and Vector Error Correction Model (VECM). The results showed that there is a long-term co-integration relationship among the variable prices on the levels of fishermen, wholesalers, and Ternate City retailers and Bitung City retailers. Based on the results of long-term VECM testing, the retail market in Ternate City and South Halmahera Regency Wholesale Market are tightly integrated. Whereas in the retail market of the  Bitung city and the cakalang market at the fishermen level are cointegrated very weakly where every price change in the Ternate retail market will negatively affect prices at the level of Bitung city fishermen and retailers. In the short term, price formation at the fishermen level is only influenced by prices at Ternate retailers and not influenced by prices at the level of wholesalers and retailers in Bitung City.